Downhill skiing injury fatalities among children. Issue 2 (5th April 2004) - Xiang, H; Stallones, L; Smith, G A
Abstract : Objective: Young skiers are at increased risk for injury, however, epidemiological data on skiing related fatal injuries among child skiers are scarce. This study aimed to provide information needed to develop injury control and prevention programs. Design and setting: Study subjects came from Colorado, USA and were identified using a death certificate based surveillance system. Fatal injuries were limited to events that occurred at established commercial ski resorts in Colorado, and subjects were classified as child skiers (0–17 years) or adult skiers (⩾18 years). Main outcome measure: Type and external cause, time, and week day of injury, gender and residency of the decedents. Results: During the study period from 1980–2001, 149 fatal injuries associated with downhill skiing were identified; 21 (14.1%) occurred among child skiers aged ⩽17 years. The age of the youngest decedent was 7 years. In females the proportion of fatal injuries among child skiers was nearly three times that of adults. Traumatic brain injuries were the leading cause of death (67% of all deaths) among children, while multiple internal injuries and traumatic brain injuries accounted for almost equal proportions of fatal injuries among adults. Collision was the leading external mechanism of fatal injuries, accounting for more than two thirds of fatal injuries in both child and adult skiers. Conclusions: Traumatic brain injury was the leading cause and collision was the leading external injury mechanism of fatal injuries associated with downhill skiing among child skiers. This underscores the importance of brain injury prevention strategies, including the use of ski helmets and prevention of collisions on ski slopes.